FPGA implementation made easy for applied digital signal processing courses - Kehtarnavaz, N.; Mahotra, S. (2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2011)
Applied digital signal processing courses offered at many universities do not normally include FPGA implementation of signal processing algorithms. This is due to the fact that students taking applied signal processing courses often are not familiar with FPGA programming languages and as a result FPGA implementation cannot be easily achieved in one-semester long applied digital signal processing courses. In this paper, we present an approach for making FPGA implementation easily achievable within one-semester long applied digital signal processing courses or within a relatively short design cycle time. Our approach is based on the LabVIEW FPGA Module which allows FPGA implementation to be achieved in a time-efficient manner via more intuitive graphical coding. An overview of our designed FPGA implementation approach covering typical laboratories that students encounter in applied digital signal processing courses is provided.